Perinatal protein deprivation facilitates morphine cross-sensitization to cocaine and enhances ΔFosB expression in adult rats - Perondi, María Cecilia (2017)
Previous studies have indicated that neural changes induced by early nutritional insult cause an altered response to pharmacological treatments, including addictive drugs. This study evaluates the influence of perinatal protein malnutrition in developing cross-sensitization to cocaine-induced rewarding effects in animals pre-exposed to morphine. Different groups of well-nourished (C-rats) and protein-deprived animals (D-rats) were treated twice a day for three days with increasing doses of morphine or with saline. After 3 days, the incentive motivational effects of cocaine were assessed in a Conditioned Place Preference paradigm in both groups. In saline pre-treated animals, dose-response curves to cocaine revealed a conditioning effect in D-rats at doses of 5, 7.5 and 10 mg/kg, while this effect was observed in C-rats only with 10 and 15 mg/kg. Furthermore, when animals of both groups were pre-treated with escalating doses of morphine, cross-sensitization to the conditioning effect of cocaine was elicited only in D-rats with low doses of cocaine (5 and 7.5 mg/kg). In contrast, under the same experimental conditions, C-rats show no cross-sensitization. To correlate this differential rewarding response with a molecular substrate linked to the behavioral changes observed after repeated drug exposure, ΔFosB expression was assessed in different brain regions. D-rats showed a significant increase in this transcription factor in the nucleus accumbens, amygdala and medial prefrontal cortex. These results demonstrated that perinatal protein deprivation facilitates rewarding effects and the development of cross-sensitization to cocaine, which correlates with an upregulation of ΔFosB in brain areas related to the reward circuitry.